PROBLEM ISSUES OF LAND RESOURCES ASSOCIATED WITH THE CONSEQUENCE OF MILITARY ACTIONS IN UKRAINE - Тітова, Світлана; Самчук, Олександра; Ковбасюк, Ярослав (SWorldJournal, 2024)
The article examines the current state and prospects for restoring Ukraine’s land resources in the context of the post-war period. The territories that were violated as a result of Russia’s large-scale aggression against Ukraine were studied and the proce